Effect of sense of coherence on oral health behavior and status: A systematic review and meta-analysis - Roksana Poursalehi; Arash Najimi; Bahareh Tahani (Wolters Kluwer Medknow Publications, 2021)
The sense of coherence (SOC) is defined as a personal orientation to life. People with higher SOC are better at dealing with stressful situations, psychological stress, and problems and are more able to manage them, leading to better general health. The purpose of this study was to evaluate the effect of SOC on the oral health status of people in different age groups. A systematic search up to May 2019 was carried out in PubMed,Scopus, Psycho info, and Persian sources. Studies were included if they evaluated the relationship between SOC and oral health behaviors (OHBs) or oral health status including dental caries. The Newcastle-Ottawa checklist was used to appraise the selected articles and meta-analysis of included studies were performed using Comprehensive Meta-Analysis software. Value of P < 0.05 was considered to be statistically significant. Odds ratio (OR) was used to measure effect size with 95% confidence interval (CI). The random-effects model was chosen in the presence of heterogenicity. I2 index and Q index were used to measure the heterogeneity present between the studies. Fifteen articles received the minimum score of criticism. In general, SOC could significantly affect the oral health and OHBs of adults independently of the underlying factors. There was a significant relationship between SOC and tooth decay in adolescents, but this association was poor after adjusting for the underlying factors. In children, only one article revealed an association with OHBs. Meta-analysis revealed that SOC was significantly associated with the caries rate (OR = 0.78, CI 95% = 0.9-0.67, P = 0.001) and tooth brushing frequency (OR = 1.22, CI 95% = 1.1-1.31 and P < 0.001). Sense of coherence appears to be one of the effective factors in predicting oral health behaviors and ultimately oral health, especially in adults. The number of articles available for children and adolescents was not sufficient in this regard.